2021
DOI: 10.3390/ijerph182312563
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Physical Activity, Work Ability, Absenteeism and Presenteeism in Australian and New Zealand Adults during COVID-19

Abstract: Public health movement and social restrictions imposed by the Australian and New Zealand governments in response to the COVID-19 pandemic influenced the working environment and may have affected health behaviours, work ability, and job performance. The aim of this study was to determine the associations between health behaviours and work ability and performance during COVID-19 restrictions and if health behaviours were related to demographic or population factors. A cross-sectional survey was used to gather re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
0
15
0
3
Order By: Relevance
“…In the present study, we assess associations with stress-related symptoms and work ability, which is defined as an index that indicates how well a person can work currently and in the near future and whether that person is able to do his or her work in terms of work demands and health resources [17]. A study of employees in Australia and New Zealand found increased sedentary behavior during COVID-19 was associated with lower work ability and job performance [18]. Another study of laboratory staff in China found work ability decreased with increased job burnout during COVID-19 [19].…”
Section: Employees' Health In Home Officementioning
confidence: 99%
“…In the present study, we assess associations with stress-related symptoms and work ability, which is defined as an index that indicates how well a person can work currently and in the near future and whether that person is able to do his or her work in terms of work demands and health resources [17]. A study of employees in Australia and New Zealand found increased sedentary behavior during COVID-19 was associated with lower work ability and job performance [18]. Another study of laboratory staff in China found work ability decreased with increased job burnout during COVID-19 [19].…”
Section: Employees' Health In Home Officementioning
confidence: 99%
“…On the contrary, a study by Hunter et al (2021) in Australia and New Zealand revealed that lower presenteeism was exhibited by those working at home than those working on site. Also, part time employees are less likely to exhibit presenteeism, and those with the existing medical condition are less likely to report good job performance.…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, the betweennessbased propagation intuitively shows that crowded places have a higher infection probability (53). The edge betweenness centrality can be defined as Equation (3). Among all the shortest paths between all OD pairs on the road network, the more paths that pass the edge, the higher betweenness centrality the edge possesses.…”
Section: Road Network Performancementioning
confidence: 99%
“…Since 2020, the global COVID-19 pandemic has not only triggered major shifts in city operations, but has also had a considerable impact on people's travel behaviors, as well as their abilities to work and their mental health (1)(2)(3)(4). Many countries have adopted strict public health control measures to contain the spread of this unprecedented and highly infectious virus, such as travel restrictions, road closures, and social distancing.…”
Section: Introductionmentioning
confidence: 99%